Estudo metodológico de caracterização física de resíduos sólidos domiciliar e comercial para o municipio de Fortaleza-CE - Lessa, Emerson Ribeiro (2008)
It can be observed that life quality of the population is directly related to income since in market economies there are essential components for the well being of families which depend from families ability to purchase products such as food, clothing etc. The present study is concerned with the determination of a methodology compatible with the reality of Fortaleza/CE, for the gathering of physical parameters of commercial and household wastes such as: production per capita, waste composition expressed in % of total weight of sample; waste density. The analysis of quality and quantity of the household and commercial wastes generated in Fortaleza is correlated to income indicators. This research provides important data for the design and implementation of plans and programmes of waste management and for the provision of services of household and commercial solid wastes. It can be concluded that generation of waste is directly related to the consumption standards of a society. The research obtained the following data for Fortaleza: per capita production of household wastes: 0,74 kg/hab/day; mass density: 218 kg/m3; around half of the household wastes is organic matter subject to composting (50,3%).